Contrasting anesthetic sensitivities of T-type Ca(2+) channels of reticular thalamic neurons and recombinant Ca(v)3.3 channels - Joksovic, Pavle M (2004)
1. Reticular thalamocortical neurons express a slowly inactivating T-type Ca(2+) current that is quite similar to that recorded from recombinant Ca(v)3.3b (α1Ib) channels. These neurons also express abundant Ca(v)3.3 mRNA, suggesting that it underlies the native current. 2. Here, we test this hypothesis by comparing the anesthetic sensitivities of recombinant Ca(v)3.3b channels stably expressed in HEK 293 cells to native T channels in reticular thalamic neurons (nRT) from brain slices of young rats. 3. Barbiturates completely blocked both Ca(v)3.3 and nRT currents, with pentobarbital being about twice more potent in blocking Ca(v)3.3 currents. Isoflurane had about the same potency in blocking Ca(v)3.3 and nRT currents, but enflurane, etomidate, propofol, and ethanol exhibited 2–4 fold higher potency in blocking nRT vs Ca(v)3.3 currents. 4. Nitrous oxide (N(2)O; laughing gas) blocked completely nRT currents with IC(50) of 20%, but did not significantly affect Ca(v)3.3 currents at four-fold higher concentrations. In addition, we observed that in lower concentration, N(2)O reversibly increased nRT but not Ca(v)3.3 currents. 5. In conclusion, contrasting anesthetic sensitivities of Ca(v)3.3 and nRT T-type Ca(2+) channels strongly suggest that different molecular structures of Ca(2+) channels give rise to slowly inactivating T-type Ca(2+) currents. Furthermore, effects of volatile anesthetics and ethanol on slowly inactivating T-type Ca(2+) channel variants may contribute to the clinical effects of these agents.